2006
DOI: 10.1111/j.1445-6664.2006.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sowing density and spatial pattern of spring wheat (Triticum aestivum) on the suppression of different weed species

Abstract: To better understand the potential for improving weed management in cereal crops with increased crop density and spatial uniformity, we conducted field experiments over two years with spring wheat (Triticum aestivum) and four weed species: lambsquarters (Chenopodium album), Italian ryegrass (Lolium multiflorum), white mustard (Sinapis alba), and chickweed (Stellaria media). The crops were sown at three densities (204, 449, and 721 seeds m −2 ) and in two spatial patterns (normal rows and a highly uniform patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 18 publications
(41 reference statements)
3
41
1
2
Order By: Relevance
“…Another study using three field corn planting densities (40,000, 70,000 and 100,000 plants ha −1 ) and three weed densities resulted in up to a 50% weed biomass reduction between the low and high field corn densities [18]. Similar results have been documented in other crop species such as wheat (Triticum aestivum), barley (Hordeum vulgare), and safflower (Carthamus tinctorius) [19][20][21].…”
Section: Introductionsupporting
confidence: 62%
“…Another study using three field corn planting densities (40,000, 70,000 and 100,000 plants ha −1 ) and three weed densities resulted in up to a 50% weed biomass reduction between the low and high field corn densities [18]. Similar results have been documented in other crop species such as wheat (Triticum aestivum), barley (Hordeum vulgare), and safflower (Carthamus tinctorius) [19][20][21].…”
Section: Introductionsupporting
confidence: 62%
“…If that is the case, there will be a trade-off between suppression of weeds and crop yield potential. Reduced weed biomass and crop yield loss because of increased crop density have also been reported in other crops (Lemerle et al 2004;Olsen et al 2006). Suppression of weed growth may also be achieved by delaying the emergence of Chinese sprangletop relative to rice.…”
Section: Resultsmentioning
confidence: 82%
“…For instance, Bulson et al (1997) found that weed biomass was significantly reduced when the densities of wheat (Triticum aestivum L.) and field bean (Vicia faba L.) intercrops were increased; and Arce et al (2009) showed that soybean seeding rates (24Á42 seeds/m 2 ) were inversely related to weed biomass. Increased seeding rates lead to quicker canopy closure, increased crop interference and greater weed suppression, resulting in increased yields (Olsen et al 2006;Kolb et al 2012). Thus, the use of increased crop density as a cultural weed management practice can complement the use of cover crops for weed suppression.…”
Section: Research Articlementioning
confidence: 99%